Design of SAP-1 controller and simulation using mentor graphics / Zamri Majid - Majid, Zamri (1999)
The control unit of the microprocessor is responsible for providing the necessary timing and control signals to all operations in a microcomputer. One technique for designing microcofflrol logic is the micropogrammed control, which derives the sequencing and control logic from the contents of a ROM. This paper presents the design of a microprogrammed control unit for a theoretical computer called the SAP-1 (Simple-As-Possible computer). The sequencer controller is designed and modeled using the Mentor Graphics Design Architect and QuickSim II package respectively